"CONTROLE SOCIAL EM SAÚDE NO MARANHÃO: análise documental" - SILVA, Glenda Pereira Costa (2023)
Popular participation has always been present at different times in the history of Brazil, leading to the achievement of important social rights, including in the health sector. Social Control in Health is a consequence of the participation of civil society in public administration and constitutes one of the principles and guidelines of the Unified Health System. The Health Councils, instituted by Law n. 8.142/90, made it possible for the decision making power in conducting public policies to be divided between Society and the State. There are also gaps in knowledge about the dynamics and composition of these collegiate bodies that have a permanent and deliberative character in the Brazilian states. Therefore, this research aimed to analyze the dynamics and composition of the instance for social control in health, from the State Health Council in the State of Maranhão. This is a documentary-type qualitative research, in which minutes of ordinary and extraordinary meetings of the State Health Council of Maranhão were analyzed, including resolutions, State Health Plans and Reports of State Conferences, during the period from 2014 to 2020 The results are presented and discussed based on two categories of analysis: CESMA: characteristics of its composition and 2. Particularities of the Public Health Budget approval process. The first indicates the changes in the distribution of seats among the entities that make up the council, after changes in the state legislation that governs this body. In the second, the agendas in which internal power struggles emerge, causing tensions between the councilors, the main one being the management of the public health budget in Maranhão. It is concluded that for a period of almost twenty years there was a predominance of low representation, originating from the lack of renewal of members, having as a negative impact the permanence of more organized groups. Weaknesses were also detected in the council's ability to monitor the Public Health Budget. The multiplicity of attributions and activities of a bureaucratic nature, for example, monitoring the rendering of accounts and approvals (or rejections) of management reports constituted a limiting factor for the performance of health counselors. Thus, the council's limited power of influence is evident in giving propositional directions on the definition of the state's health budget guidelines. In this way, the analyzed period illustrates the advances and challenges, which permeate the persistence of asymmetrical power relations that affect the democratization of the decision-making process.